The Effect of Project-Based Learning Integrated with Bulletin Board Media on Students’ Writing Skill in an EFL Context - Uksim, Muhammad (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This study aims to investigate the effect of Project-Based Learning integrated with bulletin board media on students’ writing skills in an English as a Foreign Language (EFL) context. The research employed a quasi-experimental design involving two groups: an experimental class and a control class. The experimental group was taught using Project-Based Learning integrated with bulletin board media, while the control group received conventional instruction. The participants were senior high school students, and the data were collected through writing tests administered in the form of pre-test and post-test. The students’ writing was assessed based on several aspects, including content, organization, vocabulary, language use, and mechanics. The results of the study revealed that students in the experimental class showed a significant improvement in their writing skills compared to those in the control class. This was indicated by the higher mean score in the post-test and supported by the result of the t-test analysis, which showed that the obtained t-value was higher than the t-table value at the 0.05 level of significance. The integration of bulletin board media in Project-Based Learning provided students with opportunities to actively engage in the writing process, collaborate with small groups, and present their work in a meaningful way. In conclusion, Project-Based Learning integrated with bulletin board media has a positive and significant effect on students’ writing skills in the EFL context. Therefore, this approach is recommended as an effective alternative strategy for teaching writing, as it promotes students’ motivation, creativity, and overall writing performance.